[OP.8B.02] HYPERTENSION WITHIN THE METABOLIC SYNDROME: RESULTS OF THE 40 YEAR FOLLOW UP OF THE SEVEN COUNTRIES STUDY. (September 2017) - Parapid, B.; Danchin, N.; Kanjuh, V.; Stojanovic, M.; Nedeljkovic-arsenovic, O.M.S.; Obrenovic-kircanski, B.; Simic, D.V.; Moschandreas, J.; Blackburn, H.; Menotti, A.; Adachi, H.; Kromhout, D.; et al.
Abstract : Objective: The metabolic syndrome (Met Sy) is in the focus of as a cluster of risk factors that are known to promote atherosclerosis, diabetes and obesity, primarily, while the Seven Countries Study remains one of the core epidemiological trials that taught us the basis of modifiable risk factors for coronary heart disease, mainly. Inhereted risk factors and parental morbidity and mortality was equally studied in all the participants, and we are presenting the results of the 40 years follow-up. Design and method: The Seven Countries Study encompassed 12, 763 participants who were healthy at baseline and who underwent regular check ups every 5 years throughout over 4 decades. Results: Using the IDF definition of the Metabolic Syndrome, 9.09% of participants were identified and the combination of risk factors (RF) is presented in Picture 1. Figure. No caption available. Conclusions: Hypertension was the leading risk factor in all the cohorts, irrelevant of presence or absence of MetSy and influenced 40y mortality independently, while also being the most frequent risk factor in the MetSy population.